2009
DOI: 10.1021/ma9021136
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination, Iodination, and Silylation of Poly(2,2′-dioxy-1,1′-biphenylphosphazene). New Halogenated Polyphosphazenes with Sterically Hindered Reactivity

Abstract: The polyphosphazene {[NP(O2C12H8)]} n (1) [(O2C12H8) = 2,2′-dioxy-1,1′-biphenyl] with [PO2C12H8] cycles in the repeating units reacts slowly with chlorine in concentrated sulfuric acid to give the 5,5′-chlorinated {[NP(O2C12H8)]1−x [NP(O2C12H7Cl)] x } n (2) (x = 0.2−1), with limiting oxygen index (LOI) in the interval 26−33 (estimated from the TGA residues), corresponding to potential self-extinguishing flame retardants. The reaction of 1 with [Ipy2]BF4 in CH2Cl2 in the presence of CF3SO3H gave the 5,5′-iodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The 13 C‐NMR spectra of the deuterated polymer also confirmed the presence of [NP(O 2 C 12 H 7 D )] units in polymer 3 (see the Supporting Information). The regioselectivity of the reaction at the C 3 of the [NP(O 2 C 12 H 8 )] units is not surprising since other electrophilic reactions (i.e., nitration, chlorination, and iodination) performed over the same polyphosphazene 1 , resulted in mixtures of C 3 ‐ and C 5 ‐substitutions (i.e., ortho‐ and para‐position with respect to the carbon linked to the phosphazene chain) . However, in the case of the lithiation reaction, the C 3 position can be favored by the coordination of the lithium to the nitrogen of the phosphazene main chain, as observed in the lithiation of (triphenyl)iminophosphorane derivatives of general formula Ph 3 PNSiMe 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 13 C‐NMR spectra of the deuterated polymer also confirmed the presence of [NP(O 2 C 12 H 7 D )] units in polymer 3 (see the Supporting Information). The regioselectivity of the reaction at the C 3 of the [NP(O 2 C 12 H 8 )] units is not surprising since other electrophilic reactions (i.e., nitration, chlorination, and iodination) performed over the same polyphosphazene 1 , resulted in mixtures of C 3 ‐ and C 5 ‐substitutions (i.e., ortho‐ and para‐position with respect to the carbon linked to the phosphazene chain) . However, in the case of the lithiation reaction, the C 3 position can be favored by the coordination of the lithium to the nitrogen of the phosphazene main chain, as observed in the lithiation of (triphenyl)iminophosphorane derivatives of general formula Ph 3 PNSiMe 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, TGA thermograms of polymers 4 and 5 containing PPh 2 and Bpin moieties, respectively, showed a final pyrolitic residue at 800 °C of 50% and 40% of their initial mass (see Table ). These ceramic residues are significantly larger than those of the precursor 1 (30%) and the silylated polymer 2h (32%), and can be compared with those of other polyphosphazenes containing chlorine or butylamino substituents, making them potential self‐extinguishing. The DSC traces showed that the attachment of functional groups on the C 3 of the [NP(O 2 C 12 H 8 )] units induced an increase in the T g values (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations